2007
DOI: 10.1016/j.jad.2006.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and sexual coercion among pregnant women in India: Relationship with depression and post-traumatic stress disorder

Abstract: Background-Intimate partner violence (IPV) is prevalent in most parts of the world. It is also prevalent during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
126
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 53 publications
12
126
0
5
Order By: Relevance
“…Given that a framework is needed for further progress in this arena, I defend a framework that recognizes IPV as a form of gender-based violence. Existing research on this topic demonstrates that IPV became recognized initially as a critical threat to the health of society because of the severity of consequences among female victims 1,[3][4][5][6][7][8] and the high prevalence of male-perpetrated IPV victimization among women in the United States and abroad. 4,9 By contrast, no evidence has demonstrated that female-perpetrated violence against male partners has been a threat to the health of populations of men.…”
mentioning
confidence: 99%
“…Given that a framework is needed for further progress in this arena, I defend a framework that recognizes IPV as a form of gender-based violence. Existing research on this topic demonstrates that IPV became recognized initially as a critical threat to the health of society because of the severity of consequences among female victims 1,[3][4][5][6][7][8] and the high prevalence of male-perpetrated IPV victimization among women in the United States and abroad. 4,9 By contrast, no evidence has demonstrated that female-perpetrated violence against male partners has been a threat to the health of populations of men.…”
mentioning
confidence: 99%
“…These findings are supported by a number of antenatal care studies around the world. [17][18][19][20][21] This is especially concerning given that intimate partner violence during pregnancy is also known to have mental health effects beyond the duration of pregnancy. For example, longitudinal studies have shown that experiencing intimate partner violence during pregnancy increases a woman's risk of postpartum depression, 22 and also increases the risk of the children's future behavioural and emotional problems.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of symptoms endorsed were added up. According to the manual, symptoms were coded as none, mild (1-10), moderate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate to severe (21-30) and severe (36-51). None of the women reached the highest severity score.…”
Section: Measurementmentioning
confidence: 99%
“…Investigaciones previas han demostrado que los antecedentes de abuso infantil, los trastornos psiquiátricos previos (depresión, ansiedad, abuso de alcohol o sustancias psicoactivas), la alta paridad (11), el insuficiente apoyo social, los conflictos de pareja, el embarazo no planificado (22,23), la condición de madre adolescente, primípara o soltera, el bajo nivel educacional (14) y el haber tenido algún aborto previo (24) se asociaron significativamente con las enfermedades psiquiátricas durante el embarazo. En un estudio realizado en mujeres de 14 a 37 semanas de gestación evaluadas con la EDPE en Indonesia se encontró una elevada prevalencia de depresión asociada con la dependencia de sustancias psicoactivas y los problemas familiares y de pareja (25).…”
Section: Discussionunclassified